Mississippi Bishop William Henry Elder and the Civil War - Starrett, Ryan (Civil War series., 2019)
Conquest. War. Famine. Death. During the Civil War, all Four Horsemen circled the flock of William Henry Elder, the third bishop of Natchez. Elder was a hopeful unionist turned secessionist whose diocese encompassed the entirety of Mississippi. Consequently, he witnessed many of the pivotal moments of the Civil War--the capitulation of Natchez, the Siege of Vicksburg, the destruction of Jackson and the overall desolation of a state. And in the midst of the conflict, Bishop Elder went about his daily duties of baptizing, teaching, praying, preaching, performing marriages, confirming, comforting and burying the dead. -- Provided by publisher.